O Zapomnianym świetle Jakuba Demla i jego polskim przekładzie - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2021)
Catholic priests who were practicing artistic creativity, mostly poets, in the Czech lands, formed a group called the Catholic Modern in the nineteenth century. Jakub Deml, a Czech priest, poet, and writer from Moravia, was in close contact with the group. His works were not always positively received by concurrent readers, but today he is considered a precursor of contemporary literary trends, especially surrealism. This article presents a portrait of one of the most original Czech writers of the first half of the twentieth century. The text also takes into account the issue of the Polish translation of his work Zapomenuté svĕtlo (Forgotten Light) by Andrzej Czcibor-Piotrowski and published in Wołów in 2000 by the Czarne Publishing House.